Assessment of organic Rankine cycle configurations for solar polygeneration orientated to electricity production and desalination. (August 2021) - Jaubert, Hadrien; Borel, Philippe; Guichardon, Pierrette; Portha, Jean-François; Jaubert, Jean-Noël; Coniglio, Lucie
Highlights: Modelling-Simulation of a PTCs-ORC plant for power & drinking water by RO-LTMED. RO modelling from experiments & RO brine routed to the LTMED (zero-liquid-discharge). ORC designs selected on the basis of thermal efficiency and exergy destruction rate. The best ORC design: regenerator + double-stage turbine with intermediary reheater. Green working fluid used: ORC with + 43% thermal efficiency, −18% exergy destruction. Abstract: This work addresses the polygeneration concept integrating concentrating solar power (CSP) with an organic Rankine cycle (ORC) to produce electricity and drinking water by hybrid desalination process combining reverse osmosis (RO) and low-temperature multi-effect distillation (LTMED). Experiments carried out on a bench scale RO pilot led to determine optimal operating parameters as well as options to mitigate the main limiting factors of this technology by hybridizing with LTMED. These data helped to simulate a large scale solar polygeneration plant integrating parabolic trough collectors as CSP technology and a hybrid RO-LTMED system as desalination technology. Various ORC design proposals were simulated and the optimal configuration was pointed out on the basis of thermodynamic criteria (energy efficiency and exergy destruction) and an economic analysis by using two working fluids: an alkane commonly admitted as good candidate and an ester proposed here as green alternative. Results obtained in this work contribute positively to extending the solar polygeneration for desalination and production of energy leading to future sustainable plants.